Risk of Leptospirosis in Flood Affected Areas and Environmental Health Control Measures - Fitriani, Isah; Rauf, Ihsan Jaya (Oshada, 2025)
Flooding is an environmental disaster that consistently increases the risk of environment-related diseases, including leptospirosis. As a zoonotic disease, leptospirosis frequently emerges in post-flood settings due to sanitation damage, water stagnation, and increased human exposure to environments contaminated with Leptospira. However, existing studies on leptospirosis are predominantly clinical and epidemiological, while analyses positioning the disease as a structural environmental health issue in post-disaster contexts remain limited. This study aims to analyze leptospirosis risk in flood-affected areas and to examine relevant and sustainable environmental health control strategies based on scientific evidence. A qualitative descriptive-analytical method was employed using an Evidence-Based Environmental Health Review approach, synthesizing scientific literature, institutional reports, and policy documents related to leptospirosis, flooding, and environmental health. The findings indicate that flooding acts as a primary ecological determinant shaping leptospirosis risk through sanitation disruption, water quality degradation, increased reservoir populations, and interactions with social vulnerability. Environmental health–based control strategies—such as sanitation improvement, environmental management, ecological reservoir control, community education, and early warning systems—are shown to be more effective than reactive medical responses. This study reinforces the repositioning of leptospirosis as a structural environmental health issue to support sustainable post-disaster prevention strategies.